Obtenção de manta elastomérica de base de estireno butadieno utilizando-se resíduos de borracha de pneus para a aplicação na construção civil - Pacheco, Caroline Valadão (2014)
This essay aimed to conduct a study on the rubber blanket of manufacture from waste tires. The disposal of tires has created an environmental problem, since the nature takes years to decompose them. On the other hand, the waste tire can be used on laminate flooring bases because this material has characteristics that can reduce noises that cause discomfort for the residents of buildings. This essay presents a study on the manufacture of rubber blanket using up waste tires with the purpose of reducing noise for the residents of buildings. This research becomes important both for society and for professionals and companies in general, because through it, they will have the knowledge not only about the materials, techniques and conventional processes, but they will also have a focus on how this issue of noise can be softened through materials that are often thrown on the street, polluting cities. The 50% of waste tire blanket obtained an absorption required by the regulation. The thickness of the blanket did not affect the internal height of apartment projects, because the thickness of the blanket is smaller than the expected subfloor.